A difference of blood lactate level in freestyle swimming between S-shaped and I-shaped stroke - Ito, S.; Matsumoto, T.; Daisuke Abe, D. (1st International Scientific Conference of Aquatic Space Activities, 2008)
One of the authors proved that the calculation results which showed I-shaped pull stroke in freestyle stroke: The drag pull generates the maximum impellent. While the conventional S-shaped pull stroke provides the maximum efficiency. The result obtained here is mechanical efficiency, and it is distinct for physiological efficiency. S-shaped pull is shifted easily to the anaerobic motion in a high stroke pitch with a heavy load. As a result, the blood lactate accumulates in muscles to get tired. However, with the I-shaped pull, the stroke pitch cannot get so high that the I-shaped pull is not easy to become anaerobic motion because of the heavy load to the arm originally. The authors measured the blood lactate and heart rates with both pulls at a fast speed at the almost same time with a swimmer who mastered both pulls. As a result, it was found that physical load of I-shaped pull is less than that of S-shaped pull at the same fast swimming speed.